Toward Understanding the Influence of Ethylbenzene in p-Xylene Selectivity of the Porous Titanium Amino Terephthalate MIL-125(Ti): Adsorption Equilibrium and Separation of Xylene Isomers - Mariana A. Moreira (2012)
The potential of the porous crystalline titanium dicarboxylate MIL-125(Ti) in powder form was studied for the separation in liquid phase of xylene isomers and ethylbenzene (MIL stands for Materials from Institut Lavoisier). We report here a detailed experimental study consisting of binary and multi-component adsorption equilibrium of xylene isomers in MIL-125(TO powder at low (<= 0.8 M) and bulk (>= 0.8 M) concentrations. A series of multi-component breakthrough experiments was first performed using n-heptane as the eluent at 313 K, and the obtained selectivities were compared, followed by binary breakthrough experiments to determine the adsorption isotherms at 313 K, using n-heptane as the eluent. MIL-125(Ti) is a para-selective material suitable at low concentrations to separate p-xylene from the other xylene isomers. Pulse experiments indicate a separation factor of 1.3 for p-xylene over o-xylene and m-xylene, while breakthrough experiments using a diluted ternary mixture lead to selectivity values of 1.5 and 1.6 for p-xylene over m-xylene and o-xylene, respectively. Introduction of ethylbenzene in the mixture results however in a decrease of the selectivity.